Christian Medical College And Hospital Ludhiana,Punjab. - Pandhare Sangeeta Balu (Journal for ReAttach Therapy and Developmental Diversities, 2021)
An Exploratory study was conducted to assess the knowledge of staff nurses regarding Mechanical Ventilation in Critical Care areas of Christian Medical College and Hospital, Ludhiana, Punjab. The sample size was 110 staff nurses working in Critical Care Areas and sample was selected by using non-probability sampling technique and the data was collected by using self-structured knowledge questionnaire on Mechanical Ventilation. The results showed that, 52(47.3%) staff nurses had average level of knowledge and 32 (29%) of staff nurses had good level of knowledge, while 20(18.2%) of the staff nurses had below average level of knowledge and only 6(5.5%) of the staff nurses had excellent level of knowledge regarding Mechanical Ventilation. These guidelines are prepared with the aim to enhance the knowledge of staff nurses regarding Mechanical Ventilation.